2021
DOI: 10.1101/2021.01.16.426951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selenium-dependent metabolic reprogramming during inflammation and resolution

Abstract: Trace element selenium (Se) is incorporated as the 21st amino acid, selenocysteine (Sec), into selenoproteins through tRNA[Ser]Sec. Selenoproteins act as gatekeepers of redox homeostasis and modulate immune function to effect anti-inflammation and resolution. However, mechanistic underpinnings involving metabolic reprogramming during inflammation and resolution remain poorly understood. Bacterial endotoxin lipopolysaccharide (LPS) activation of murine bone marrow-derived macrophages (BMDMs) cultured in the pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Interestingly, plasma succinate was associated with several KEGG functions directly related to succinate metabolism, such as malonate decarboxylase (EC:4.1.1.87), which inhibits succinate dehydrogenase, and isocitrate lyase (EC:4.1.3.1), and others without a direct link that might be the consequence of indirect interactions. Notably, several genes involved in selenate metabolism such as selenate reductase (EC:1.97.1.9) were found to be significantly linked to succinate and a recent publication has described selenium as a mediator of metabolic reprograming that facilitates anti-inflammation and pro-resolution [75]. Our analysis also revealed an upregulation of genes related to the phosphoenolpyruvate (PEP) node, being the most relevant phosphonopyruvate decarboxylase, which carboxylates PEP to oxalacetate and is the primary fermentative route for succinate [76] Remarkably, our study on Krebs cycle-related genes in association with fecal succinate revealed several genes significantly upregulated, with DLST (EC:2.3.1.61) and succinyl-coA synthetase (EC:6.2.1.5) being the most significant.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, plasma succinate was associated with several KEGG functions directly related to succinate metabolism, such as malonate decarboxylase (EC:4.1.1.87), which inhibits succinate dehydrogenase, and isocitrate lyase (EC:4.1.3.1), and others without a direct link that might be the consequence of indirect interactions. Notably, several genes involved in selenate metabolism such as selenate reductase (EC:1.97.1.9) were found to be significantly linked to succinate and a recent publication has described selenium as a mediator of metabolic reprograming that facilitates anti-inflammation and pro-resolution [75]. Our analysis also revealed an upregulation of genes related to the phosphoenolpyruvate (PEP) node, being the most relevant phosphonopyruvate decarboxylase, which carboxylates PEP to oxalacetate and is the primary fermentative route for succinate [76] Remarkably, our study on Krebs cycle-related genes in association with fecal succinate revealed several genes significantly upregulated, with DLST (EC:2.3.1.61) and succinyl-coA synthetase (EC:6.2.1.5) being the most significant.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found remarkable reduction of Fah expression coupled with lower levels of fumarate suggesting an altered tyrosine catabolism in Selenow −/− BMDMs. Decreased levels of fumarate is also reminiscent of a disrupted TCA cycle as previously reported in selenium deficient BMDMs, where no selenoproteins, including SELENOW, were expressed [ 13 , 36 ]. Inhibition of succinate dehydrogenase (SDH-A) with dimethylmalonate in mice maintained on selenium replete diets increased the time for resolution in a model of peritonitis indicating that decreased fumarate is a sign of disrupted metabolism and resolution [ 13 ].…”
Section: Discussionmentioning
confidence: 81%
“…Decreased levels of fumarate is also reminiscent of a disrupted TCA cycle as previously reported in selenium deficient BMDMs, where no selenoproteins, including SELENOW, were expressed [ 13 , 36 ]. Inhibition of succinate dehydrogenase (SDH-A) with dimethylmalonate in mice maintained on selenium replete diets increased the time for resolution in a model of peritonitis indicating that decreased fumarate is a sign of disrupted metabolism and resolution [ 13 ]. Together, these results imply that SELENOW may play a role in arginine and tyrosine metabolism.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations